Analysis of Pieces in The Application of Extreme Programming (XP) Methods in Laravel-Based Website Development - Luthfiana, Tias Hafidzotul; Iskandar, Joko; Sari, Yayak Kartika (Fakultas Teknik Universitas Lambung Mangkurat, 2026)
This research focuses on developing a website that can facilitate students, lecturers, heads of study programs, and study program staff in accessing relevant and up-to-date information. The problem experienced by the Informatics Study Program is the unavailability of a functional and informative website to support academic needs in the Informatics Study Program. The method used in this research uses the Extreme Programming (XP) approach with the stages of planning, designing, coding, testing which involves data collection through interviews, observations, and literature studies. The results of the analysis using the PIECES (Performance, Information, Economy, Control, Efficiency, and Service) method show the need for a website that meets user needs and is responsive to requests. The results of website development using the extreme programming method show that the website built is able to increase efficiency and effectiveness in providing services on demand. The development was carried out through four iterations, each of which included system analysis, system creation, and system testing. In each iteration process, improvements and enhancements were made to the website in accordance with the needs identified in the testing process and feedback from users. This truly reflects that the website has successfully met user needs and is responsive.